The Kepuasan jamaah haji Kabupaten Rembang menggunakan Importance Performance Analysis (IPA) - Silfia Nurul Farahdina; Mirwan Surya Perdhana; Lusi Rachmiazasi Masduki (MBR (Management and Business Review), 2021)
The Indonesian government's service for organizing regular pilgrimages from year to year still shows various problems. This study aims to determine the satisfaction of the pilgrims by analyzed the quality of service for Hajj group 56 at Rembang Regency in 2019, as well as to determine the aspects to improve the quality of Hajj services. The data used in this study was primary data obtained from a survey conducted by distributing questionnaires to the Hajj group 56 pilgrims in 2019 in Rembang Regency. The methodology used in this research was Importance Performance Analysis (IPA) method. The results of the analysis show that the highest value of satisfaction was found in the dimensions of physical evidence (tangibles), namely lodging accommodations in Mecca and Medina. While the lowest satisfaction value was found in the empathy dimension.